2015
DOI: 10.5194/piahs-369-25-2015
|View full text |Cite
|
Sign up to set email alerts
|

A Tri-National program for estimating the link between snow resources and hydrological droughts

Abstract: Abstract. To evaluate how summer low flows and droughts are affected by the winter snowpack, a Tri-National effort will analyse data from three catchments: Alpbach (Prealps, central Switzerland), Gudjaretis-Tskali (Little Caucasus, central Georgia), and Kamenice (Jizera Mountains, northern Czech Republic). Two GIS-based rainfall-runoff models will simulate over 10 years of runoff in streams based on rain and snowfall measurements, and further meteorological variables. The models use information on the geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…About 60-62% of the groundwater is recharged from snowmelt (unweighted mixing approach), when snowfall only accounts for 40-45% of the total annual precipitation. This has also been previously suggested elsewhere in the European Alps (Cervi et al, 2015;Penna et al, 2014Penna et al, , 2017Zappa et al, 2015). To conclude, HydroMix provides a Bayesian approach to mixing model problems in hydrology that takes full advantage of small sample sizes.…”
Section: Discussionsupporting
confidence: 53%
“…About 60-62% of the groundwater is recharged from snowmelt (unweighted mixing approach), when snowfall only accounts for 40-45% of the total annual precipitation. This has also been previously suggested elsewhere in the European Alps (Cervi et al, 2015;Penna et al, 2014Penna et al, , 2017Zappa et al, 2015). To conclude, HydroMix provides a Bayesian approach to mixing model problems in hydrology that takes full advantage of small sample sizes.…”
Section: Discussionsupporting
confidence: 53%
“…In general, they found that the snowmelt yield to groundwater recharge per unit of precipitation is higher than that of rain‐induced recharge. The dominance of snowmelt‐induced groundwater recharge has been shown in the United States (Earman et al, ; O'Driscoll et al, ; Rose, ; Simpson et al, ; Winograd et al, ), in Canada (Jasechko et al, ; Maule et al, ; Mountain et al, ), in the Himalayas (Jeelani et al, ), in Switzerland (Halder, Decrouy, & Vennemann, ), in Spain (Kohfahl et al, ), in Georgia (Zappa et al, ), in Italy (Cervi et al, ; Penna, Engel, et al, ; Penna et al, ), and in Chile (Herrera et al, ). A recent analyses (Jasechko et al, ; Jasechko & Taylor, ) of published stable isotope data with the help of a global hydrologic model suggest that spring snowmelt due to winter precipitation dominates recharge in temperate and arid climates.…”
Section: Focus On Selected Snow Hydrological Processesmentioning
confidence: 97%
“…An impressive number of studies (Cervi et al, 2015;Earman et al, 2006;Herrera et al, 2016;Jasechko et al, 2014;Jasechko & Taylor, 2015;Jasechko, Wassenaar, & Mayer, 2017;Jeelani, Bhat, & Shivanna, 2010;Kohfahl et al, 2008;Lechler & Niemi, 2012;Maule, Chanasyk, & Muehlenbachs, 1994;Mountain, James, & Chutko, 2015;O'Driscoll et al, 2005;Penna, Engel, et al, 2014;Penna et al, 2017;Rose, 2003;Simpson, Thorud, & Friedman, 1970;Winograd et al, 1998;Zappa et al, 2015) have used a stable isotope approach to attribute percentages of snow and rain as sources for annual groundwater recharge (see a summary in Table 1). In general, they found that the snowmelt yield to groundwater recharge per unit of TABLE 1 Summary of studies estimating groundwater recharge from summer (rain) and winter precipitation (snow), along with the used snow end member, that is, snowfall or snowmelt or a combination of the two…”
Section: Estimating the Contribution Of Rain Versus Snow To Streamfmentioning
confidence: 99%
“…Recent snowmelt modelling approaches at the catchment scale do not, however, explicitly simulate snowpack outflow during rain-on-snow events (Ala-aho et al, 2017;Lyon et al, 2010;Smith et al, 2016), or use stable water isotopes to track the flow pathways (Kormos et al, 2014;Marks et al, 2001;Rössler et al, 2014;Storck et al, 1998). Our spatiotemporally distributed isotope measurements could thus be beneficial for testing and improving existing snowmelt models (Zappa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%